Ancient and Medieval North Pole Stars: A Review and New Identifications - Mozaffari, S. Mohammad (JAOS, 2024)
In this article, the identification in different civilizations and eras of some cir-umpolar stars as the north pole star are reviewed, the main principles behind and crucial considerations in the past for forming the criteria for north pole star identification are scrutinized, and some profound differences in ancient and medieval views of it are discussed. The point of departure is the identification of the north polar star in Euclid’s Phaenomena as the star HR 4646, and its identification in the Pahlavi Bundahišn and al-Ṣūfī’s Ṣuwar al-kawākib as HR 4893. Because of the inevitable transitory nature of the north pole star, the location of al-Ṣūfī’s north pole star in the manuscript tradition of his magnum opus during the centuries after him is also investigated in detail. A supplementary discussion is included on the confusion between two different entities—the pole of the celestial sphere and the pivot of an indigenous Arabic asterism envisioned as a millstone—in philological, lexical, and literary Islamic works, which chiefly stems from the vague terminology employed.